101 tips for a zero-waste kitchen - Kellogg, Kathryn (Countryman Press, an imprint of W.W. Norton & Company, 2024)
"In America, more than 20 percent of all food waste comes from residential kitchens. Here's how you can make a difference right now. The average family of four spends $1,500 a year on food that they don't eat. It's time to make better choices that can make your kitchen routines better for the planet, more manageable, and even more enjoyable. Not sure where to start or what to do? Kathryn Kellogg shows you how to plan and prep effectively. She provides scores of practical, easy-to-follow tips and recipes"--